2021
DOI: 10.3389/fphys.2021.706359
|View full text |Cite|
|
Sign up to set email alerts
|

Chrysophanol Relieves Cisplatin-Induced Nephrotoxicity via Concomitant Inhibition of Oxidative Stress, Apoptosis, and Inflammation

Abstract: Cisplatin (CDDP) is one of the most frequently prescribed chemotherapy medications. However, its nephrotoxicity which often leads to acute kidney injury (AKI), greatly limits its clinical application. Chrysophanol (CHR), a mainly active anthraquinone ingredient, possesses various biological and pharmacological activities. In this study, we aimed to investigate the underlying protective mechanisms of CHR against CDDP-induced AKI (CDDP-AKI) using C57BL/6 mouse and human proximal tubule epithelial cells. In vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Our data revealed that CHR could reduce hemin-induced oxidative stress in HT22 cell; this result is similar to the role of CHR in other diseases. For example, Ma et al reported that CHR relieves cisplatin-induced nephrotoxicity via concomitant inhibition of oxidative stress and apoptosis [62]. Zhao et al demonstrated that CHR alleviates nitrosation/oxidative stress injury in focal cerebral ischemia/reperfusion [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that CHR could reduce hemin-induced oxidative stress in HT22 cell; this result is similar to the role of CHR in other diseases. For example, Ma et al reported that CHR relieves cisplatin-induced nephrotoxicity via concomitant inhibition of oxidative stress and apoptosis [62]. Zhao et al demonstrated that CHR alleviates nitrosation/oxidative stress injury in focal cerebral ischemia/reperfusion [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that chrysophanol alleviated cisplatin (CDDP)-induced acute kidney injury (AKI). Its pharmacological mechanism may primarily act through the inhibition of CDDP-induced oxidative stress, apoptosis and the NF-κB signaling pathway ( Ma et al, 2021 ).…”
Section: Inhibitory Effects Of the Natural Ingredients On Renal Fibrosismentioning
confidence: 99%
“…Another study demonstrated that chrysophanol alleviated cisplatin (CDDP)-induced acute kidney injury (AKI). Its pharmacological mechanism may primarily act through the inhibition of CDDP-induced oxidative stress, apoptosis and the NF-κB signaling pathway (Ma et al, 2021). Studies have found that aloe-emodin can reduce the protein levels of PI3K, Akt and mTOR in UUO mice, improve biochemical indicators such as Scr and BUN in UUO mice, and inhibit the mRNA expression of TGF-β1, collagen type I, collagen type IV and FN.…”
Section: Inhibition Of Inflammation Apoptosis and Oxidative Stressmentioning
confidence: 99%